Access to rehabilitation services for families of children with disabilities in Ghana - Hasehni Vampere; Ebenezer Dassah; Rebecca Tawiah; Melody A. Quarm (Rehabilitation Advances in Developing Health Systems)
Background: Early rehabilitation interventions can significantly mitigate the effects of disabilities in children as they grow older. However, families of children with disabilities (CWDs) in resource-deprived settings face limited opportunities to access rehabilitation services for their children resulting in largely unmet rehabilitation needs.